Soluble mimics of the cytoplasmic face of the human V1-vascular vasopressin receptor bind arrestin2 and calmodulin - Wu, Nan; Macion-Dazard, Rosemarie; Nithianantham, Stanley; Xu, Zhen; Hanson, Susan M; Vishnivetskiy, Sergey A; Gurevich, Vsevolod V; Thibonnier, Marc; Shoham, Menachem (Molecular pharmacology, 2006)
Signal transduction by G protein-coupled receptors (GPCRs) is mediated by interactions between intracellular proteins and exposed motifs on the cytoplasmic face of these receptors. Arrestins bind to GPCRs and modulate receptor function either by interfering with heterotrimeric G protein signaling or by serving as signaling adaptors themselves. Calmodulin interacts with GPCRs triggering a calcium response. We have studied the interaction of arrestin2 and calmodulin with intracellular elements of the human V1-vascular vasopressin receptor (hV1R). For this purpose, we designed, expressed, and purified soluble fusion proteins with the maltose-binding protein (MBP) from Escherichia coli that mimic the intracellular surface of the hV1R. These MBP fusion proteins bind arrestin2 and calmodulin with affinities in the micromolar range. A different series of soluble receptor analogs, named vasopressin receptor 1 elements on a soluble scaffold (V1ROSS) proteins, consist of the third intracellular loop and/or the C-terminal segment of the hV1R receptor juxtaposed on the surface of the MBP. V1ROSS proteins bind calmodulin and a truncated, phosphorylation-independent form of arrestin2 more tightly than the corresponding linear fusion proteins. Thus, embedding receptor loops within the three-dimensional structure of the MBP yields a better representation of the active conformation of these receptor loops than linear receptor peptides fused onto the C terminus of the MBP. V1ROSS proteins provide a valuable tool to study receptor interactions because they are more amenable to structural analysis than the native membrane receptor. These findings set the stage for the detailed structural analysis of these protein-protein interactions that are important for understanding the mechanism of signaling.